Mechanical Durability Assessment of an Energy-Harvesting Piezoelectric Inverted Flag - Kaidong Yang; Andrea Cioncolini; Mostafa R. A. Nabawy; Alistair Revell (Energies, 2021)
This paper presents results from a practical assessment of the endurance of an inverted flag energy harvester, tested over multiple days in a wind tunnel to provide first insights into flapping fatigue and failure. The inverted flag is a composite bimorph, composed of PVDF (polyvinylidene difluoride) strips combined with a passive metallic core to provide sufficient stiffness. The flag, derived from an earlier, more extensive study, flaps with a typical amplitude of ~120 degrees and a frequency of ~2 Hz, generating a constant power of ~0.09 mW in a wind velocity of 6 m/s. The flag was observed to complete ~<semantics>5×105</semantics> cycles before failure, corresponding to ~70 h of operation. The energy generated over this lifespan is estimated to be sufficient to power a standard low-power temperature sensor for several months at a sampling rate of one sample/minute, which would be adequate for applications such as wildfire detection, environmental monitoring, and agriculture management. This study indicates that structural fatigue may present a practical obstacle to the wider development of this technology, particularly in the context of their usual justification as a ‘deploy and forget’ alternative to battery power. Further work is required to improve the fatigue resistance of the flag material.